Diplospermy II indicated as the origin of a liveborn human triploid (69, XXX). Issue 5 (October 1981) - Page, B M; Robson, E B; Cook, P J; Sanger, R; Watt, J L
Abstract : A 69, XXX liveborn baby was shown to have the Rh genotype CDe/cDE/cde which suggested that 46 of her chromosomes were of paternal origin. Studies on C band polymorphisms and other genetic markers indicated that the most likely origin of this triploid was a failure of male meiosis II.